Անկարելի զոհ մը վերընծայելու պայքարը՝ Գրիգոր Նարեկացիի կոթողական փորձը լեզուի ընդմէջէն - Կիւլլիւճեան, Յակոբ («Նաիրի» հրատ.)
Although the 10th century Armenian poet St. Gregory of Narek‟s magnum opus, the Book of Tragedy or Lamentations, is somehow overlooked in the context of European medieval mystical literature, it offers unique solutions to many problems faced by most mystic writers. This paper focuses on the ways Gregory deals with the ineffability and with the impossibility of language, given that his declared purpose is to make his poetry a “rational sacrifice”. An extensive reading list from the great names of mysticism will only highlight the unusual approaches by the poet-theologian-philosopher. Instead of employing text as usual in an attempt to convey the mystical experience, or the desire for union, he culminates in shaping that experience within the text itself, explicitly identifying himself with the book. Performative language renders speach not only as a vehicle for union with God, but also as the place and the act where it happens.
Keywords: Լեզուաբանութիւն; Գրիգոր Նարեկացի